PENGARUH PROFITABILITAS TERHADAP KEBIJAKAN DIVIDEN - Yuliyanti, Leni (JURNAL PENDIDIKAN AKUNTANSI & KEUANGAN, 2013)
The core of the dividend policy is to determine the proportion of the net income to be distributed as dividend, so in theory dividends are determined by the size of the net income. This study examines the effect of profitability on dividend policy PT. Bank Central Asia, Tbk. the purpose of this study is to reveal the profitability of PT. Bank Central Asia, Tbk as measured by Return On Equity (ROE), how is the dividend policy of PT. Bank Central Asia, Tbk as measured by Dividend Payout Ratio (DPR), and to determine the effect of profitability on dividend policy of PT. Bank Central Asia, Tbk. This research method used is descriptive method verification. The data used are secondary data from the financial statement of PT. Bank Central Asia, Tbk during 2002-2011. The statistical analysis used was correlation analysis of product moment using manual calculation and SPSS v.20 software for windows. The results showed that describe of profitability PT. Bank Central Asia, Tbk, which is proxied by Return On Equity (ROE) showed a downward trend with an average ROE of 6.27%, dividend policy overview PT. Bank Central Asia, Tbk, which is proxied by the Dividend Payout Ratio (DPR) showed a downward trend with an average of 43.39% DPR, as well as the positive effect on the profitability of the dividend policy of PT Bank Central Asia Tbk and the magnitude of these effects is equal to 62.09 % and 37.91% influenced by other factors is the rights issue and liquidity factors. Therefore, PT. Bank Central Asia, Tbk should trying to improve profitability, especially in the aspect of ROE in order not to continue to decline, then be careful and consider aspects of financial performance, especially profitability in setting dividend policy so that the dividend can provide a positive signal to investors that a conflict of interest between investors and management can be minimized.